Experimental Study of the Effect of Air Flow Rate Variation on the Three-Phase Flow Characteristics in the Uplift Section of an Airlift Pump - Rahayu, Yunita; Mujiarto, Sigit; Fajarningrum, Nurmala Dyah; Saleh, Arif Rahman (Universitas Sultan Ageng Tirtayasa, 2025)
A three-phase airlift pump is a pumping system that utilizes compressed air to lift fluid and solid particles, widely used due to its efficiency and minimal mechanical components. The injected air flow rate plays a crucial role in influencing the flow pattern, velocity, and phase distribution within the system. This study aims to examine the effect of varying air flow rates on the three-phase flow characteristics in an airlift pump with a 15° injector angle, including the critical condition, superficial velocity of each phase, flow patterns, and changes in solid, gas, and liquid hold-up values. Experiments were conducted with air flow rates ranging from 30 to 60 LPM and a water column height of ¾ h. Data were analyzed using image processing techniques to calculate flow velocity and hold-up. Based on the experimental results, it was found that the solid hold-up increased from 0.7592 to 0.9030, and gas hold-up from 0.0531 to 0.0819, while liquid hold-up decreased from 0.1877 to 0.0151 as the air flow rate increased. The superficial liquid velocity also rose from 0.056 m/s to 0.158 m/s, with the value recorded at 50 LPM representing the most optimal operating condition of the airlift pump and serving as the ideal reference for system operation. This research is expected to contribute to the development of airlift pump applications in industrial applications..